Design and test of a biomechanical model for the estimation of knee joint angle during indoor rowing: Implications for FES-rowing protocols in paraplegia - Vieira, T.; Cerone, G. L.; Gastaldi, L.; Pastorelli, S.; Oliveira, L. F.; Gazzoni, M.; Botter, A. (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2018)
Functional electrical stimulation of lower limb muscles during rowing provides a means for the cardiovascular conditioning in paraplegia. The possibility of shaping stimulation profiles according to changes in knee angle, so far conceived as changes in seat position, may help circumventing open issues associated with muscle fatigue and movement coordination. Here, we present a subject-specific biomechanical model for the estimation of knee joint angle during indoor rowing. Anthropometric measurements and foot and seat positions are inputs to the model. We tested our model on two samples of elite rowers; 15 able-bodied, and 11 participants in the Rio 2016 Paralympic games. Paralympic rowers presented minor physical disabilities (LTA-PD classification), enabling them to perform the full rowing cycle (with legs, trunks, and arms). Knee angle was estimated from the rowing machine seat position, measured with a linear encoder, and transmitted wirelesslyto a computer. Key results indicate the root mean square error (RMSE) between estimated and measured angles did not depend on group and stroke rate (p > 0.267). Significantly greater RMSE values were observed, however, within the rowing cycle (p <; 0.001), reaching on average 8 deg in the mid-recovery phase. Differences between estimated and measured knee angle values resulted in slightly earlier (5%) detection of knee flexion, regardless of the group and stroke rate considered. Offset of knee extension, knee angle at catch and range of knee motion were identified equally well with our model and with inertial sensors. These results suggest our model describes accurately the movement of knee joint during indoor rowing.